Impact of anomalous forest fire on aerosol radiative forcing and snow cover over Himalayan region. (February 2017) - Bali, Kunal; Mishra, Amit Kumar; Singh, Sachchidanand
Abstract: Forest fires are very common in tropical region during February–May months and are known to have significant impact on ecosystem dynamics. Moreover, aerosols emitted from these burning activities significantly modulate the Earth's radiation budget. In present study, we investigated the anomalous forest fire events and their impact on atmospheric radiation budget and glaciated snow cover over the Himalayan region. We used multiple dataset derived from satellites [Moderate Resolution Spectroradiometer (MODIS) and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO)] and reanalysis models [Global Fire Assimilation System (GFAS), Second Modern-Era Retrospective analysis for Research and Application (MERRA-2) and ERA-interim] to evaluate the effect of biomass burning aerosols on radiation budget. April 2016 is associated with anomalous fire activities over lower Himalayan region in the last fourteen years (2003–2016). The model estimated organic carbon (OC) and black carbon (BC) emission reaches up to ∼3 × 10 4 and ∼2 × 10 3  μg/m 2 /day, respectively during the biomass burning period of April 2016. The meteorological data analysis accompanied with CALIOP aerosol vertical profile shows that these carbonaceous aerosols could reach up to ∼5–7 km altitude and could be transported towards glaciated region of upper Himalayas. The large amount of BC/OC from biomass burning significantly modulates the atmospheric radiation budget. The estimated columnar heating rate shows that these carbonaceous aerosols could heat up the atmosphere by ∼0.04–0.06 K/day in April-2016 with respect to non-burning period (2015). The glaciated snow cover fractions are found to be decreasing by ∼5–20% in 2016 as compared to long term mean (2003–2016). The combined analyses of various climatic factors, fires and associated BC emissions show that the observed snow cover decrease could be results of increased surface/atmospheric temperature due to combined effect of large scale climatic changes and BC absorption. Our results suggest that biomass burning can have significant effects on the Himalayan region, particularly in view of its importance in hydrological cycle and ecosystem. Highlights: Anomalous fires are observed in April 2016 over Himalaya in last 14 years. Fire-derived BC/OC aerosols are transported over Himalayan glaciers. Carbonaceous aerosols could heat up Himalayan atmosphere by 0.04–0.06 K/day. Meteorological changes & BC absorption lead to ∼5–20% decrease in snow cover.